Increased water use efficiency and water productivity of arabidopsis by abscisic acid receptors from Populus canescens. (8th January 2019) - Papacek, Michael; Christmann, Alexander; Grill, Erwin
Abstract: Background and Aims: Water deficit is the single most important factor limiting plant productivity in the field. Poplar is a crop used for second-generation bioenergy production that can be cultivated on marginal land without competing for land use in food production. Poplar has a high demand for water, which makes improving its water use efficiency (WUE) an attractive goal. Recently, we showed that enhanced expression of specific receptors of arabidopsis for the phytohormone abscisic acid (ABA) can improve WUE in arabidopsis and water productivity, i.e. more biomass is formed per unit of water over time. In this study, we examined whether ABA receptors from poplar can enhance WUE and water productivity in arabidopsis. Methods: ABA receptors from poplar were stably introduced into arabidopsis for analysis of their effect on water use efficiency. Physiological analysis included growth assessment and gas exchange measurements. Key Results: The data presented here are in agreement with the functionality of poplar ABA receptors in arabidopsis, which led to ABA-hypersensitive seed germination and root growth. In addition, arabidopsis lines expressing poplar RCAR10, but not RCAR9, showed increased WUE by up to 26 % compared with the wild type with few trade-offs in growth that also resulted in higher water productivity during drought. The improved WUE was mediated by reduced stomatal conductance, a steeper CO2 gradient at the leaf boundary and sustained photosynthesis resulting in an increased intrinsic WUE (iWUE). Conclusions: The analysis is a case study supporting the use of poplar ABA receptors for improving WUE and showing the feasibility of using a heterologous expression strategy for generating plants with improved water productivity.